2015
DOI: 10.1111/hpb.12433
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of transarterial chemoembolization in patients with transjugular intrahepatic portosystemic shunts

Abstract: TACE is an effective treatment strategy for HCC in TIPS patients; albeit may be associated with higher complication rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…TACE takes the advantage of the hepatic dual blood supply resulting in emboli-zation of the tumor-feeding hepatic arteries, while portal venous flow to normal hepatocytes is preserved[15]. TACE in TIPS patients may be associated with increased hepatotoxicity[16]. This important change in the blood supply may aggravate hepatic necrosis[17], and when arteries that supply HCC are embolized, many factors can compensate for liver failure[18].…”
Section: Discussionmentioning
confidence: 99%
“…TACE takes the advantage of the hepatic dual blood supply resulting in emboli-zation of the tumor-feeding hepatic arteries, while portal venous flow to normal hepatocytes is preserved[15]. TACE in TIPS patients may be associated with increased hepatotoxicity[16]. This important change in the blood supply may aggravate hepatic necrosis[17], and when arteries that supply HCC are embolized, many factors can compensate for liver failure[18].…”
Section: Discussionmentioning
confidence: 99%
“…TACE has emerged as an effective treatment strategy for patients with HCC. Although TACE was an effective treatment strategy for HCC with TIPSS, Miura et al [ 18 ] proved that TACE might be associated with higher complication rates for patients who are treated with TIPSS. Thus, we excluded the patients treated with TACE.…”
Section: Discussionmentioning
confidence: 99%
“…13 Another retrospective cohort study of 16 patients with TIPS who underwent conventional TACE procedures reported grade 3 or 4 hepatobiliary SAEs in 25% of patients. 14 Kohi et al retrospectively compared the incidence of hepatotoxicity within 30 days of conventional TACE for HCC between 10 patients with TIPS and 148 controls. BCLC stage was 0/A in 60% of patients in the TIPS group and 63% of the control group; however, a high proportion of patients in both groups had baseline Child-Pugh class B or C liver function (50% in the TIPS group, 72% in the control group).…”
Section: Discussionmentioning
confidence: 99%